Logics of Government Innovation and Reform Management in China - Husain, Lewis (STEPS centre, 2015)
Since the beginning of reforms in the late 1970s, China has developed rapidly, transforming itself into a middle-income country, raising hundreds of millions out of poverty and, latterly, developing broad-based social protection systems. The country’s approach to reform has been unorthodox, leading many to talk of a specific Chinese model of development. This paper analyses the role of innovation (chuangxin) and experimentation in the Chinese government repertoire and their contribution to management of change during the rapid, complex and interconnected reforms that China is undergoing. ‘Innovation’ is understood as the process of generation, putting into use, and spread, of new ideas. This contemporary focus on innovation is an extension of an older Chinese government attachment to sub-national initiative in policy formulation and development that goes back to the beginnings of the PRC and before. Central government backing for, and endorsement of, proactive agency on the part of sub-national governments responds to a belief that China is too large, and conditions around the country too diverse, to allow adoption of ‘one size fits all’ policy. Sub-national governments are expected to show initiative in adapting policy locally, and creating locally-useable policy solutions within the overall scope of central policy mandates/ paradigms. The paper argues that innovation by sub-national government is systemically embedded: while central government sets the policy agenda, local governments are frontline managers, and develop a range of policy practices. Differences in conditions between localities mean that multiple variant policy practices are often in circulation at any one time. While innovation is not quantifiable in the aggregate, there is much controlled experimentation, freewheeling innovation, and trial and error, all of which are part of a search for new policy fixes and institutional solutions. Many forms of policy transfer and learning are in evidence, including much central learning from sub-national models, as well as sub-national circulation of a range of innovative policy practices. While much government innovation is not ‘original’, and may be ‘inefficient’ or of little systemic usefulness, overall, the churn of government innovation remains valuable in underpinning systemic adaptation and reform. The paper situates the analysis of government innovation within a larger framework on the functioning of Chinese government and international literature on policy transfer, and outlines an agenda for future research on the structural bases of Chinese government innovation and its contribution to adaptive management.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

The Whistler principles to accelerate innovation for development impact - G7 (G7, 2018)
The Whistler principles to accelerate innovation for development impact : 2018 G7 Summit – Canada 2018 G7 Presidency – Charlevoix, Quebec